Antibacterial Solution Using Cinnamomum verum (Cinammon) and Cympobogon citratus (Lemongrass) Essential Oils with Hydrogen Peroxide Against Staphylococcus aureus and Escherichia coli - Montañer, Janelle Sasha O. (Animo Repository, 2023)
Amidst the pandemic, millions of impoverished Filipinos lack sufficient access to sanitation services that protect them from bacterial infections. As such, this study endeavored to formulate a disinfectant spray of hydrogen peroxide and varying concentrations of lemongrass (Cymbopogon citratus) and cinnamon (Cinnamomum verum) essential oils to produce a maximally effective solution. Due to their natural origin, these essential oils were chosen for their extensive antibacterial properties, affordable price, and low toxicity levels. Six disinfectant spray solutions containing different concentrations of either essential oil were tested against Staphylococcus aureus and Escherichia coli bacteria through the agar disk diffusion method. After analyzing the data using mean, standard deviation, and MANOVA, it was found that including cinnamon and lemongrass essential oil had no statistically significant effect on the antibacterial activity of the hydrogen peroxide solution, regardless of the concentration of essential oil used, p > 0.05. However, the lemongrass samples were slightly more effective than the cinnamon solutions. Thus, future researchers are encouraged to investigate other components that can potentially increase the antibacterial activity of a disinfectant spray.